2022
DOI: 10.47191/ijsshr/v5-i9-52
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Academic Supervision toward Learning Quality through Competence and Work Motivation of Teachers in A-Accredited Public Senior High Schools in Barito Kuala

Abstract: The quality of education in Barito Kuala is still below the standard and illustrates that the learning quality in senior high school is not maximum. Therefore, this study aims to analyze: teacher academic supervision toward learning quality throu gh competence and work motivation of teachers in A-Accredited Public High Schools in Barito Kuala. This study employed a quantitative descriptive research with a total sample of 124 teachers of Public Senior High Schools with A-accredited in Barito Kuala. The data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This success will increase if the academic supervision skills of the leader of teaching institutions are used not only to evaluate teacher performance in controlling the teaching and learning process, but also to assist teachers in improving their performance. (Wahyu & Saleh, 2022) revealed that the participation of teachers in training, be it In House Training as well as external training can improve the professional abilities of teachers.…”
Section: B Principal Development Strategy In Developing Teacher Pedag...mentioning
confidence: 99%
“…This success will increase if the academic supervision skills of the leader of teaching institutions are used not only to evaluate teacher performance in controlling the teaching and learning process, but also to assist teachers in improving their performance. (Wahyu & Saleh, 2022) revealed that the participation of teachers in training, be it In House Training as well as external training can improve the professional abilities of teachers.…”
Section: B Principal Development Strategy In Developing Teacher Pedag...mentioning
confidence: 99%